Hydrogen Absorption in Weldments of Overlaid Claded Pressure Vessel - Rusli, Ronnie Higuchi (Makara Journal of Technology, 2008)
Cracks was found in type 347 stainless steel internal attachment welds of a reactor for a high temperature, and high pressure hydrogen service. One of the possible causes of cracking is low cycle fatigue cracking induced by repetition of thermal stress to embrittled weld metal. Type 347 weld metal loses its ductility by presence of sigma phase and hydrogen.